TEACHER PROFESSIONAL LEARNING IN PURSUIT OF THE COMMON GOOD: A DISCUSSION OF THE ROLE OF DEMONSTRATION SCHOOLS IN TEACHER EDUCATION - Loughland, Tony (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2012)
The Federal Government in Australia has recently established Centres for Excellence in Teacher Education. These Centres represent a power shift towards schools in teacher education and away from centralised bureaucracies and university faculties of education. Given this shift, it is interesting to examine other historical and current school-based models of teacher education, specifically demonstration schools in the United Kingdom, United States, and Australia and professional development schools in the United States. This paper discusses both models with a detailed case study of the operation of one demonstration school in Sydney, Australia. The discussion and case study reinforces the lessons of the historical models that initiatives in this area need long-term support so that they can develop the momentum necessary to achieve the long-term cultural change required. LA FORMATION PROFESSIONNELLE DES ENSEIGNANTS COMME RECHERCHE DU BIEN COMMUN : DISCUSSION DU RÔLE DES ÉCOLES DE STAGES DANS LA FORMATION DES ENSEIGNANTS Le gouvernement fédéral de l’Australie a récemment mis sur pied des Centres d’excellence en formation des enseignants. Ces centres représentent un transfert de pouvoirs dans le domaine de la formation des enseignants, des bureaucraties centralisées et facultés universitaires vers les écoles. En regard de ce changement, il est intéressant de faire l’examen d’autres modèles de formation des enseignants en milieu scolaire. Historiques ou actuels, les modèles étudiés sont les écoles de stages d’Angleterre, des États-Unis et de l’Australie ainsi que les écoles de développement professionnel américaines. Cet article présente les deux modèles ainsi qu’une étude de cas détaillée sur les opérations d’une école de stages située à Sydney en Australie. La présentation des deux modèles et l’étude de cas supportent les leçons tirées des modèles historiques. En effet, ceux-ci soutiennent que les initiatives dans ce domaine requièrent un support à long terme pour développer le dynamisme nécessaire à la concrétisation des changements culturels requis à long terme.